STRUKTUR KOMUNITAS DIPLOPODA TANAH PADA KETINGGIAN BERBEDA DI PERKEBUNAN TEH KABAWETAN BENGKULU - Darmi, Darmi; Ezatalopa, Mentari; Rizwar, Rizwar (Jurnal Biosilampari : Jurnal Biologi, 2023)
Soil diplopods are an important biotic component in agricultural land ecosystems. Its presence in the soil is an important in the decomposition process of soil organic matter, and plays a role in increasing soil fertility. This study aims to study the community structure of soil Diplopoda at different altitudes in the Bengkulu Kabawetan Tea Plantation. The location of the study used the stratified sampling method which is based on the altitude of 800 m, 900 m and 1000 m above sea level. Soil Diplopods were collected by using the 50x50 cm quadratic method and a 100 m line transect. Data analysis consisted of density, relative density, diversity index, and Morisita index. There were 4 types of soil Diplopods in the Bengkulu Kabawetan Tea Plantation, namely Arthrosphaera sp., Gyrodrepanum sp., Oxidus sp., and Trigoniulus sp. At an altitude of 900 m and 1000 m, 4 species of Diplopoda were found and at an altitude of 800 m consisted of 3 types of Diplopoda. The density of soil diplopods at the three study locations varied, with the highest density at an altitude of 1000 m followed by at an altitude of 800 m and at 900m. The diversity index at the three locations is low and moderate. The distribution of diplopods at the study site was random and uniform.